Representation of Gender-Based Violence Words in Genshin Impact - I.G.N Adhimas Maharditya (Humanitatis : Journal of Language and Literature, 2023)
This paper aims to examine a representation of gender-based violence words inside video games. This study focused on processing textual data inside video games, where Genshin Impact’s in-game textual data is the chosen object of research. In previous research regarding modern media, gender male was always related to violence words more than female. Uncovering the result from the comparison of violence words used Genshin between males and females is the main goal of this study. Genshin was chosen because of the dominant number of female characters (33) compared to male characters (17), which piqued my curiosity if this game is able to change the culture where female characters can be more related to violence words. A mixed-method analysis is used as the core method of this research, as aside from statistical analysis by corpus software, culture, and social aspects are also analyzed based on statistical results. The result shows that despite a big difference in character count, male characters still have more relation to violence words than female characters by around 2%.